(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Inthis paper we present about impact of human resource management between publicand private sector banks. Human resources are well thought-out as a foundationof sustainable competitive advantage. The accomplishment of an organizationdepends upon several factors but the most vital factor that affects theassociation performance is its employee.